ANALISIS KEBIJAKAN PERUSAHAAN DAN PARTISIPASI TENAGA KERJA PADA BAGIAN PRODUKSI TERHADAP PENERAPAN 5R PT. MARITIM BARITO PERKASA - Ghandy Elmada Setyanto (The Indonesian Journal of Occupational Safety and Health, 2015)
ABSTRACT5R is a program to minimize or eliminate the danger by treating a workplace correctly. A good work and comfortable environment should be arranged so that workers can work without distractions. A good housekeeping will being held if the workers participate and obey all rules in the company not only just participate, but also contribute management of the company for 5R implementation. This study aims to analyze company’s policy dan participate of workers on sector production with 5R implementation in PT. Maritim Barito Perkasa Banjarmasin. This study used a cross-sectional design. Research on samples used 20 samples who are all of worker in sector production. The result of the research showed that 5R policy of PT. Maritim Barito Perkasa has not written. The knowledge level of workers were mostly understand about 5R implementation of PT. Maritim Barito Perkasa. And attitude that shown by workers about 5R implementation also good. Underliner of this research can be suggested to company is to make a written policy about 5R implementation. Forming audit team can be conducted every 3 month to help applying 5R implementation. 5R implementation must be supported from every side so that problem about 5R implementation can be realized maximally and continously.Keywords: worker’s participation, company policy, 5R implementation